Energy-based hydro-economic modeling of climate change effects on the Upper Euphrates Basin - Aytac, Ayca; Dogan, Mustafa Sahin; Tuna, M. Cihat (Iwa Publishing, 2024)
Climate change and global warming are expected to have effects on water resources management and planning, requiring adaptations to changing conditions. Therefore, it is very important, especially for decision-makers, to identify demand deficits due to less water availability with climate change that may occur in the existing water supply system in advance. FEHEM, a hydroeconomic optimization model of the integrated reservoir system of the Upper Euphrates Basin, which is the largest and main basin providing water flow to the Euphrates River, is developed. Using a 45-year historical hydrological dataset, water management and hydroelectric operations are evaluated with a linear programming model at monthly time steps. The effects of climate change on the Upper Euphrates Basin are evaluated under low and high carbon emission scenarios. According to the average of the different climate scenarios studied in the model, the average decrease in flows is 37.5%. With climate change, peak flows will occur about 1-2 months earlier on average. As a result of these hydrological changes, the total amount of energy production in the basin will decrease by about 54% and energy revenue by the same percentage. HIGHLIGHTS Two climate scenarios, one with high and the other with low emissions, were studied in the Upper Euphrates Basin. In both scenarios, there was a 37.5% reduction in flows on average. Moreover, the production of 10 large storage hydroelectric power plants in the Upper Euphrates Basin will decrease by approximately 50% according to different climate scenarios.
Keywords: climate change; FEHEM; hydroelectric generation; optimization model